1990
DOI: 10.1007/bf02244239
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related effects of selective 5-HT2 receptor antagonists on slow wave sleep in humans

Abstract: The effects of the selective 5-HT2 receptor antagonists, ritanserin (1, 5 and 10 mg) and ICI 169.369 (50 and 100 mg), were studied on the sleep EEG of healthy volunteers using home-based Medilog 9000 cassette monitoring. Ritanserin (5 and 10 mg) produced a significant increase in slow wave sleep (SWS) while ICI 169,369 also increased SWS but only at a dose of 100 mg. These findings are consistent with the proposal that selective 5-HT2 receptor blockade increases SWS in humans; however, the data cannot exclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The increases in slow wave sleep induced by pimavanserin were consistent with the increases in slow wave sleep induced by ritanserin 15,16,17,18 and eplivanserin 25 . The results also were consistent with a 5-HT 2A receptor mechanism underlying slow wave sleep.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The increases in slow wave sleep induced by pimavanserin were consistent with the increases in slow wave sleep induced by ritanserin 15,16,17,18 and eplivanserin 25 . The results also were consistent with a 5-HT 2A receptor mechanism underlying slow wave sleep.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, pimavanserin has been shown to increase NREM sleep in rats (unpublished observations). In humans, ritanserin, a 5-HT 2 receptor antagonist, has been shown to increase slow wave sleep in healthy volunteers after a single dose 15,16,17,18 and after repeated administration 19 . Ritanserin also increases slow wave sleep in younger 20 and older 21 poor sleepers, and in a variety of patient populations including those with depression 22 , dysthymic disorder 23 , and generalized anxiety disorder 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The view that 5-HT, receptor antagonists should be regarded as modulators of slow-wave sleep (11) is underscored by the present results. In humans ritanserin as well as seganserin have also been shown to increase slow-wave sleep (10,17,18,26). Idzikowski et al (18) showed that ritanserin enhanced the proportion of deep slow-wave sleep, whereas Ujszaszi (31) proved that sleepiness in healthy subjects was significantly increased in parts of the day with a high sleep propensity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in both rodents and humans, slow-wave sleep (SWS) is increased by the selective 5-HT 2 receptor antagonist ritanserin in a dose-dependent manner; in contrast, the selective 5-HT 2 receptor agonist meta-chlorophenylpiperazine produces the opposite effect (Idzikowski et al, 1986). Additional evidence supporting a role for 5-HT 2 receptors in sleep comes from the use of various antipsychotic agents known to promote SWS in both humans and rats (Dugovic and Wauquier, 1987;Sharpley et al, 1990;Monti and Monti, 2004). For example, the atypical antipsychotic drugs risperidone and olanzapine increase SWS in both schizophrenic and healthy subjects, respectively (Dursun et al, 1999;Sharpley et al, 2000;Yamashita et al, 2002).…”
mentioning
confidence: 99%